Artificial Intelligence (AI)-Based Pronunciation Checker: An Alternative for Independent Learning in Pandemic Situation - Sari Dewi Noviyanti (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2020)
The primary aim of this study was to explore the effectiveness of using artificial intelligence-based pronunciation checker in learning pronunciation independently from the viewpoints of higher education students of English Education Department in IAIN Jember. The students’ (n=30) opinions were collected through a questionnaire and the results of this study demonstrated that students have a varied of conceptions about using technology of doing independent learning especially in English pronunciation. The study suggests that while students admit the effectiveness of artificial intelligence technology in learning pronunciation independently, they still believe that having a real communication, especially with natives as frequently as possible, will help their pronunciation learning faster and better.